Pengaruh cecotropes kelinci terhadap kinetika produksi gas rumen in vitro - Hanifah Nurhaliza Nurhaliza; Hunafa Jalwa Adiwinata; Hanafi Abdillah; Muhammad Badar; Mansyur; Muhammad Zam Zam Syakir Niami; Ahmad Naufal Jauhari; Yulianri Rizki Yanza (Fakultas Pertanian Universitas Majalengka, 2026)
The search for natural feed additives that can enhance ruminal fermentation efficiency has gained growing attention in sustainable ruminant production research. Rabbit cecotropes contain microbial metabolites, fermentation by-products, enzymes, and microbial biomass that may support their use as a postbiotic-rich feed ingredient. This study evaluated the effects of rabbit cecotrope supplementation on the kinetics of in vitro ruminal gas production. Four dietary treatments, namely 0% (P0 as control), 5% (P1), 10% (P2), and 15% (P3) rabbit cecotropes, were incubated using the in vitro gas production technique. Cumulative gas volume was recorded every two hours over a 24-hour incubation period and fitted to the model Y = a + b(1−e⁻ᶜᵗ), where (a) denotes gas production from the rapidly soluble fraction, (b) denotes gas production from the insoluble but fermentable fraction, and (c) denotes the fractional rate of gas production. Data were analyzed using PROC MIXED of SAS together with orthogonal polynomial contrasts. Rabbit cecotrope supplementation significantly affected all kinetic parameters (p≤0.001). Parameter (a) increased linearly from −2.53 ml in P0 to 0.52 ml in P3, while parameter (b) declined from 195.0 ml to 109.3 ml. Parameter (c) increased from 0.034 h⁻¹ in the control to 0.051 h⁻¹ in both P2 and P3. The simultaneous increase in a and c alongside the decline in b indicates a shift toward faster fermentation dynamics. These findings suggest that rabbit cecotropes have potential as a postbiotic-rich feed ingredient that can modulate ruminal fermentation kinetics.